Kapitel XXXIII der anonymen arabischen Chronik Kashf al-Ghumma al-Jāmiʿ li-Akhbār al-Umma betitelt Akhbār Ahl ʿOmān min awwal Islāmihim ilā’khtilāf Kalimatihim - Klein, Hedwig (1938)
An edition of the text, with notes. On the basis of a MS in the Auslandhochschule in Berlin. This chronicle contains 40 chapters. Chapter 4 deals with the legendary immigration of the Yemeni Azd to Oman and the expulsion of the Persians. Chapters 23-29 picture the history of Oman (with many lacunas) from the beginning of Islam to Shaʿbān 1140/March 1728. In fact, the historical description ends with chapter 28; chapter 29 deals with the biographies of some of the Prophet’s companions and of some Omani and non-Omani great Ibāḍī scholars. Chapter 23 treats the history of Oman in the first three centuries of Islam. Chapter 24 deals with the opinions of several Ibāḍī scholars towards the parties in the religious-political civil war which broke out towards the end of the third century A.H.
Reprint Cairo: Dār al-Faḍīla, 2003, (24x17 cm.).*
Keywords: Sources – Oman